Description of Klebsiella spallanzanii sp. nov. and of Klebsiella pasteurii sp. nov. - Merla, Cristina; Rodrigues, Carla; Passet, Virginie; Corbella, Marta; Thorpe, Harry A.; Kallonen, Teemu V. S.; Zong, Zhiyong; Marone, Piero; Bandi, Claudio; Sassera, Davide; Corander, Jukka; Feil, Edward J.; et al. (Frontiers in Microbiology, 2019)
Klebsiella oxytoca causes opportunistic human infections and post-antibiotic haemorrhagic diarrhoea. This Enterobacteriaceae species is genetically heterogeneous and is currently subdivided into seven phylogroups (Ko1 to Ko4, Ko6 to Ko8). Here we investigated the taxonomic status of phylogroups Ko3 and Ko4. Genomic sequence-based phylogenetic analyses demonstrate that Ko3 and Ko4 formed well-defined sequence clusters related to, but distinct from, Klebsiella michiganensis (Ko1), Klebsiella oxytoca (Ko2), K. huaxiensis (Ko8) and K. grimontii (Ko6). The average nucleotide identity of Ko3 and Ko4 were 90.7% with K. huaxiensis and 95.5% with K. grimontii, respectively. In addition, three strains of K. huaxiensis, a species so far described based on a single strain from a urinary tract infection patient in China, were isolated from cattle and human faeces. Biochemical and MALDI-ToF mass spectrometry analysis allowed differentiating Ko3, Ko4 and Ko8 from the other K. oxytoca species. Based on these results, we propose the names Klebsiella spallanzanii for the Ko3 phylogroup, with SPARK_775_C1T (CIP 111695T, DSM 109531T) as type strain, and Klebsiella pasteurii for Ko4, with SPARK_836_C1T (CIP 111696T, DSM 109530T) as type strain. Strains of K. spallanzanii were isolated from human urine, cow faeces and farm surfaces, while strains of K. pasteurii were found in faecal carriage from humans, cows and turtles.